Modelling of hydrological impact of large scale conversion from rubber to oil palm plantation - Noradila Rusli @ Ruslik, 1984-; Mohammad Rafee Majid; Fakulti Alam Bina (2015)
Thesis (Ph.D (Perancangan Bandar dan Wilayah)) - Universiti Teknologi Malaysia, 2015